The Loss-of-Function S267F Variant in HBV Receptor NTCP Reduces Human Risk for HBV Infection and Disease Progression. (14th June 2018) - An, Ping; Zeng, Zheng; Winkler, Cheryl A
Abstract: Background: Sodium taurocholate cotransporting polypeptide (NTCP, SLC10A1 ) is a hepatocyte receptor for hepatitis B virus (HBV) infection. The natural NTCP S267F variant causes loss of NTCP HBV receptor function. We assessed the association of S267F with HBV resistance, HBV infection clearance, and HBV-related cirrhosis and hepatocellular carcinoma (HCC). Methods: We tested the effects of S267F in 1117 Han Chinese patients with various HBV infection outcomes using multivariate logistic regression analysis. Results: The frequency of S267F (T allele) was higher in HBV-resistant healthy controls (n = 179, 4.0%) compared to HBV-infected patients (n = 648, 1.5%); odds ratio (OR) 0.32 (95% confidence interval [CI] 0.15–0.68; P = .003; dominant model). 267F variant genotypes were also associated with reduced risk for cirrhosis (n = 192, 0.5%) and HCC (n = 258, 1.0%) compared to those with chronic HBV infection (n = 202, 3.0%); OR 0.15 (95% CI, 0.03–0.70) and OR 0.21 (95% CI, 0.062–0.72), respectively. There was no association of the S267F variant with spontaneous HBV clearance. Conclusion: The S267F variant for the HBV cell-entry receptor NTCP was associated with increased resistance to HBV infection and decreased risk for cirrhosis and liver cancer among those with chronic HBV infection. Abstract : The NTCP S267F variant diminishes the HBV receptor function of NTCP. This genetic epidemiological study of a full-spectrum HBV outcomes cohort demonstrated its association with human resistance to HBV infection and progression from chronic infection to liver cirrhosis or cancer.